Cloning, Sequencing and Expression of the Brucella Melitensis Novel Lomr Protein - Othman Jamal Nassrullah1 , Mohammed Omer Mohammad2, Shwan Kamal Rachid3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aim: Brucellosis is a zoonotic infection transmitted from animal to human directly by the animal or indirectly from their products. It is worldwide distribution especially in the middle east including Iraq and Kurdistan Region. Materials and methods: The gene coding for the outer membrane protein assembly factor LomR of 18kDa, now designated of Brucella melitensis 16M was cloned and sequenced. Cloning of insert DNA from bacteria into pET-28+ allowed the selection of a plasmid bearing a 5.5-kb NcoI fragment that seemed to contain the entire omp gene under control of its own promoter. Results: LomR was localized within a region between the NcoI and XhoI insert of approximately 396 bp. The reliability of the constructed plasmid was established by restriction enzyme mapping and sequencing. LomR was expressed after induction with IPTG in Escherichia coli BL21. Recombinant LomR was purified by chromatography through Ni-agarose. Sequencing of this region revealed an open reading frame of 390 bp encoding a protein of 132 amino acids and a predicted molecular mass of 20 KDa. Conclusion: The availability of recombinant LomR and the identification of the antigenic determinant recognized will allow the evaluation of their potential protective activity and their potential for the development of subunit vaccine against brucellosis.